Joaquim Gomes de Souza e as disparidades no reconhecimento acadêmico no Brasil e na Europa - Coury, Aline Germano Fonseca (2022)
The history of mathematics in Brazil maintained an almost mythical image of Joaquim Gomes de Souza (1829-1864), a Brazilian mathematician who received his doctoral degree in Mathematics in 1848. Acclaimed and considered a genius in Brazil, this mathematician had his works rejected in the scientific academies in Europe. This research aims to study his papers Mémoire sur la détermination de fonctions inconnues qui rentrent sous le signe d’intégration définie (1855) and On the determination of unknown functions which are involved under definite integrals (1856), submitted to the Royal Society of London and the Académie de Sciences de Paris, respectively. This study associates mathematical and sociological aspects of the referee’s report on the paper submitted. Does the mathematical correctness justify the non-recommendation to publication, or could it be related with discrimination or other political interferences in the decision? How can we comprehend the mismatch between his national recognition, on one hand, and the rejection in Europe, on the other? We shall use methods and concepts of historiography and sociology of science, including the prosopography and history of mathematics. The field theory of Bourdieu is used to identify the position of this Brazilian and other Europeans mathematicians in the social space. The results indicates that the rejection is due more to social reasons rather than the mathematics developed by Souzinha.